Análise híbrida da interação mútua escoamento/campo magnético na região de entrada de um canal de placas paralelas - Assad , Gustavo Elia (2016)
The aim of this work deals with the analysis of the mutual interaction between flow and magnetic fields that develops in a parallel-plate channel as soon as an external magnetic field is applied transversely to the plates. The fluid, electrically conductive, enters the channel under any velocity profile and will have its natural development within the channel changed by the applied magnetic field. With a coupled two-way interaction, the field will also be affected by the flow. The study of these interactions will be made from the two-dimensional version of the steady-state Navier-Stokes equations in the stream function formulation, coupled with the transport equation of the magnetic field. The solution of the governing equations will be obtained by the Generalized Integral Transform Technique (GITT). The results obtained for the velocity field, magnetic field and temperature field, as well as the associated scalar functions, are produced and compared with the literature on the basis of the main parameters of government: Reynolds number (Re), magnetic Reynolds number (Rem) and Hartmann number (Ha). In order to illustrate the consistency of the generalized integral transform technique, convergence analysis, are also performed and presented.